Osteocyte transcriptome mapping identifies a molecular landscape controlling skeletal homeostasis and susceptibility to skeletal disease - Scott E. Youlten (Nature Portfolio, 2021)
Osteocytes are the master regulatory cells within the skeleton. Here, the authors map the transcriptome of osteocytes from diverse skeletal sites, ages and between sexes and identify an osteocyte transcriptome signature associated with rare skeletal disorders and common complex skeletal diseases.